2020
DOI: 10.1088/1757-899x/962/4/042096
|View full text |Cite
|
Sign up to set email alerts
|

Phytoremediation potential of aquatic plants in Uzbekistan for the treatment of cyanide-containing wastewater

Abstract: For over a century now, the mining industry has been using cyanides for gold and silver recovery. Cyanides are highly toxic for human beings, animals, and aquatic organisms. The available physical and chemical methods of wastewater treatment are cost-ineffective. Certain microorganisms are capable of use cyanides as sources of carbon and nitrogen and turn those into ammonia and carbonate. Some plants are also efficient for the processes of cyanides destruction. Phytoremediation of cyanides may be efficient, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…From the foregoing, one can find the roots of equations ( 15)-( 18) using methods for solving boundary value problems for solving partial differential equations [11][12][13][14][15][16][17][18][19]. In order to start the calculations, it is necessary to set the initial boundary requirements.…”
Section: Resultsmentioning
confidence: 99%
“…From the foregoing, one can find the roots of equations ( 15)-( 18) using methods for solving boundary value problems for solving partial differential equations [11][12][13][14][15][16][17][18][19]. In order to start the calculations, it is necessary to set the initial boundary requirements.…”
Section: Resultsmentioning
confidence: 99%
“…Employees of the Department of Industrial Ecology and Life Safety of the IrNITU on the basis of the FGBU SEU FPS IPL for the Irkutsk region (testing fire laboratory) conducted a study of the properties of coal mined at the deposits of the Irkutsk region, as a result of which it was found that during forced heating, various coals have different dynamics of the development of smoke emission and spontaneous combustion [25]. There are also reasons to believe that the dynamics of the formation of tracer gases will also differ for different coals.…”
Section: System For the Prevention Of Spontaneous Combustion Of Coal ...mentioning
confidence: 99%
“…The positive definiteness of 𝑉𝑉�Δ, Δ𝑘𝑘 � � � � 0and 𝑉𝑉 � �Δ, Δ𝑘𝑘 � � � � 0, as well as the boundedness of the function 𝑉𝑉�Δ, Δ𝑘𝑘 � � �and variables e, Δ, Δ𝑘𝑘 � � (see (17)), ensure that they remain bounded. In addition, over time, the quadratic form 𝑉𝑉�Δ, Δ𝑘𝑘 � � �tends to a finite limit at 𝑡𝑡 𝑡 ∞ [18][19][20].…”
Section: 𝑉𝑉 � �δ δ𝑘𝑘mentioning
confidence: 99%